MORE PROPERTIES ON FLEXIBLE GRADED MODULES - Moh’D, Fida; Refai, Mashhoor (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we study the structure of flexible graded modules over various types of graded rings such as first strong and augmented graded rings. Also, we introduce the notions of flexibly simple and flexibly Noetherian modules, and investigate various properties of such modules.